Functional and Clinical Impact of Novel Tmprss6 Variants in Iron‐Refractory Iron‐Deficiency Anemia Patients and Genotype–Phenotype Studies. Issue 11 (10th September 2014) - De Falco, Luigia; Silvestri, Laura; Kannengiesser, Caroline; Morán, Erica; Oudin, Claire; Rausa, Marco; Bruno, Mariasole; Aranda, Jessica; Argiles, Bienvenida; Yenicesu, Idil; Falcon‐Rodriguez, Maria; Yilmaz‐Keskin, Ebru; et al.
<x xml:space="preserve">Abstract</x> Iron‐refractory iron‐deficiency anemia (IRIDA) is a rare autosomal‐recessive disorder caused by TMPRSS6 mutations and characterized by hypochromic microcytic anemia, low transferrin saturation, and inappropriate high levels of the iron hormone hepcidin. We report 17 novel mutations in 21 new IRIDA patients. Functional studies indicate that TMPRSS6 mutations fully or partially abrogate hepcidin inhibition. Genotyping IRIDA patients help in predicting IRIDA severity and may be useful for predicting response to iron treatment. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>